The difficulties facing the students about to graduate in applying psychological tests: A field study on a sample of students of clinical psychology at the university of Ghardaia - Mezaour, Nassima; Nadjar, djamel; Ouled himouda, djamaa (Journal of Human Sciences, 2022)
The current study aims to highlight some of the difficulties that psychology students face in applying psychological tests, and the study sample included 30 bachelor's and master's students, we focused on the descriptive approach to its suitability for this study. We also relied on the interview and clinical observation made through the professors' field practice such as accompaniment and as research supervision and graduation notes. The results of the study were that these difficulties are due to other subjective and objective factors.